Object discrimination and reversal learning in babies in the age group of 18-24 months old in dyadic interactions - Prithviraj, Ray (Nanyang Technological University, 2022)
Baby brains grow dynamically in the first 1000 days of their lives. It is during these 1000 days that 80 percent of their brain development occurs which makes these 3 years the most important for lifelong health, learning, and success. The pregnant mother’s health, nutrition and stress levels can also have an effect on the future of the baby. After the baby is born, their environment, nutrition, and social interactions also Early intervention also helps a child build self-regulation and communication skills that sets them on a path of success from the start, as this is the period when the flexibility of the brain is highest. Using sensors to understand the behaviour of parent-child dyads in controlled tasks as well as free social interactions can lead to potential early prediction of anomalies and brain disorders, therefore enabling the use of early interventions and therapeutics to react earlier and potentially prevent or reduce the intensity of the disorders. This research paper describes one such task known as the picturebook task which tests the object discrimination and reversal learning capabilities in a child, based on the learning and unlearning of rules in a time controlled setting. Demonstration of adaptability of rules in this case plays a part in the development of executive functions, the analysis of which in dyadic interactions is the overall goal of the LEAP 1kD program by Wellcome. The use of technology to detect these abilities and the reaction to the growth of such abilities is of utmost importance, therefore conducting such tasks in sensor array installed suites enables the recording of multiple parameters like Reaction Time (RT), reaching length, pointing accuracy, realisation potentials, and more. This specific task was conducted by the development of a very intuitive app which can be easily used by a toddler between the age group of 18-24 months. The data logged from the app along with EEG and video data help us understand the growth of executive functions in a longitudinal setting. Future works would include the development of more such diagnostic tools in accessible form factors of technology, which can be easily deployable over the world and can form a thorough and holistic understanding of the psychological health of the toddler.